Captivity-associated variations in fecal testosterone and progesterone metabolite concentrations in mountain gazelle (Gazella gazella) - Karaer, Mina Cansu; Kankılıç, Tolga; Tavşanoğlu, Çağatay; Vake, Tilen; Dovč, Alenka; Snoj, Tomaž (Frontiers in Veterinary Science, 2025)
BackgroundMountain gazelle (Gazella gazella) is a medium-sized antelope native to arid regions that is currently listed as an endangered species. There are only two known populations of mountain gazelles worldwide, one of which is in Hatay (Türkiye). In this study, we investigated the differences in the fecal concentrations of testosterone and progesterone metabolites in free-ranging and captive mountain gazelle.MethodsFecal samples were collected from the ground in the Hatay Mountain Gazelle Wildlife Development Area, located in Hatay Province (Türkiye) during each season of the year. In total, 246 samples, 170 from free-ranging population and 76 from captive population, were collected and used to determine testosterone and progesterone metabolite concentrations. The metabolites were extracted from dried fecal samples using methanol, and their concentrations were quantified using ELISA. The detection methods were partially validated. The analytical validation includes the determination of coefficients of variation, sensitivity of the measurements, recovery rate, linearity and cross-reactivity. In biological evaluation, the predicted reproductive status of the animals was compared with the concentrations of the progesterone and testosterone metabolites in feces.Results and conclusionOur analysis revealed that fecal samples obtained from free-ranging individuals consistently contained higher levels of testosterone metabolites than those obtained from the captive individuals. No consistent pattern was detected for fecal progesterone metabolites. Our results suggest that a constant supply of water stimulates intestinal transit. Therefore, due to faster intestinal transit the population with continuous water availability throughout the year (captive population) has lower concentrations of fecal hormone metabolites. These findings are relevant not only for the mountain gazelle as a species of endangered status but also provide important information regarding the mechanisms underlying the dynamics of steroid hormone excretion in ruminants.